Ni3Al-based single crystal alloy and preparation method and application thereof, clamp and preparation method and application thereof
By increasing the content of Al and Ta elements, increasing the volume fraction of the γˊ phase, and replacing part of Re with Mo, Ni3Al-based single crystal alloy was designed, which solved the problem that existing creep fixtures could not be used for a long time in an environment above 1220°C, and achieved low-cost and efficient production of the alloy and excellent high-temperature resistance.
Patent Information
- Application Number
- CN202411730015.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-11-28
Smart Images

Figure CN119553369A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of single crystal alloys, and in particular relates to a Ni3Al-based single crystal alloy and a preparation method and application thereof, a fixture and a preparation method and application thereof. Background Art
[0002] The temperature bearing capacity of creep fixtures is constantly improving with the development of high-temperature alloys for hot end parts of gas turbines and aircraft engines; the creep temperature of materials for high-pressure hot end parts of gas turbines and low-pressure hot end parts of aircraft engines usually does not exceed 1000°C, and the fixture materials used for creep tests on such materials are mainly K46 represented by equiaxed crystals and DZ125 represented by columnar crystals. For aircraft engines with relatively high thrust-to-weight ratios (thrust-to-weight ratios of 10 to 15), the service temperature of their high-pressure hot end parts is usually around 1100°C, and the preferred fixture materials for creep tests on such materials are single crystal high-temperature alloys represented by DD3 and DD5. For advanced aircraft engines with a thrust-to-weight ratio of 15 or above, the service temperature of the hot end components must reach 1200°C or even above 1220°C. Although the fixture materials used for creep tests on this type of material can be made of high-generation 4th and 5th generation single crystals, the temperature limit of 4th and 5th generation single crystals is around 1180°C, which cannot meet the requirements of long-term use at 1220°C. Secondly, the mass percentage of Re and Ru in high-generation single crystal alloys is as high as 8%, which is too expensive to be used in large quantities as creep fixture consumables. Summary of the invention
[0003] In view of this, the present invention provides a Ni3Al-based single crystal alloy and a preparation method and application thereof, a fixture and a preparation method and application thereof. The Ni3Al-based single crystal alloy provided by the present invention has good temperature resistance, can serve for a long time in an environment of 1220°C, and can be used as a fixture to detect the temperature resistance of high-temperature resistant alloys; and the Ni3Al-based single crystal high-temperature alloy provided by the present invention contains a small amount of Re, which reduces the production cost and is conducive to large-scale production.
[0004] In order to solve the above technical problems, the present invention provides a Ni3Al-based single crystal alloy, comprising the following element components in percentage by mass:
[0005]
[0006]
[0007] Preferably, the following element components are included in percentage by mass:
[0008]
[0009] The present invention also provides a method for preparing the Ni3Al-based single crystal alloy described in the above technical solution, comprising the following steps:
[0010] Mixing the materials according to the element ratio and smelting them to prepare a master alloy;
[0011] Remelting the master alloy and then performing single crystal casting to obtain an alloy blank;
[0012] The alloy blank is subjected to solution treatment and aging treatment in sequence to obtain the Ni3Al-based single crystal alloy.
[0013] Preferably, the temperature of the solution treatment is 1290-1335° C., and the holding time is 20-30 hours.
[0014] Preferably, the aging treatment includes a primary aging treatment and a secondary aging treatment performed sequentially;
[0015] The temperature of the primary aging treatment is 1000-1100°C, and the holding time is 2-4h;
[0016] The temperature of the secondary aging treatment is 850-900° C., and the insulation time is 30-34 hours.
[0017] Preferably, the crystal pulling rate of the single crystal casting is 1 to 5 mm / s.
[0018] The present invention also provides the use of the Ni3Al-based single crystal alloy described in the above technical solution or the Ni3Al-based single crystal alloy prepared by the preparation method described in the above technical solution in a fixture used for preparing and testing the temperature resistance of the alloy.
[0019] The present invention also provides a clamp, comprising a base and a gasket;
[0020] The substrate comprises a first Ni3Al-based single crystal alloy and a PtAl coating coated on the surface of the first Ni3Al-based single crystal alloy;
[0021] The gasket comprises a second Ni3Al-based single crystal alloy and a HY3 coating and a YSZ ceramic layer which are sequentially laminated and coated on the surface of the second Ni3Al-based single crystal alloy;
[0022] The first Ni3Al-based single crystal alloy and the second Ni3Al-based single crystal alloy are the Ni3Al-based single crystal alloy described in the above technical solution or the Ni3Al-based single crystal alloy prepared by the preparation method described in the above technical solution.
[0023] The present invention also provides a method for preparing the clamp described in the above technical solution, comprising the following steps:
[0024] Processing the Ni3Al-based single crystal alloy to obtain a matrix model and a gasket model respectively;
[0025] Plating Pt, removing hydrogen, diffusing Pt and infiltrating Al are sequentially performed on the surface of the substrate model to obtain the substrate;
[0026] Spraying HY3 coating and YSZ ceramic layer on the surface of the gasket model in sequence to obtain the gasket;
[0027] The base and the gasket are assembled to obtain the clamp.
[0028] The present invention also provides the use of the fixture described in the above technical solution or the fixture prepared by the preparation method described in the above technical solution in detecting the temperature resistance of alloys.
[0029] The present invention provides a Ni3Al-based single crystal alloy, comprising the following elemental components in percentage by mass: 7.0-8.3wt.% Al, 2.0-3.8wt.% Ta, 7.9-9.8wt.% Mo, 0.8-1.5wt.% Re and the balance Ni. The Ni3Al-based single crystal alloy provided by the present invention has good temperature resistance, a long-lasting life of more than 120h at 1220°C, and an effective service life of not less than 1000h at 1220°C. The present invention increases the volume fraction of the γˊ phase in the Ni3Al-based single crystal alloy by increasing the content of Al and Ta elements, and uses Mo to replace Re in a high mismatch alloying design, thereby significantly reducing the cost of the alloy while improving the temperature bearing capacity of the Ni3Al-based single crystal alloy.
[0030] The present invention also provides a fixture, including a substrate and a gasket; the substrate includes a first Ni3Al-based single crystal alloy and a PtAl coating coated on the surface of the first Ni3Al-based single crystal alloy; the gasket includes a second Ni3Al-based single crystal alloy and a HY3 coating and a YSZ ceramic layer sequentially laminated and coated on the surface of the second Ni3Al-based single crystal alloy; the first Ni3Al-based single crystal alloy and the second Ni3Al-based single crystal alloy are the Ni3Al-based single crystal alloys described in the above technical solution or the Ni3Al-based single crystal alloys prepared by the preparation method described in the above technical solution. In the present invention, the Pt-modified Al coating can inhibit the aggregation of S at the interface between the oxide film and the coating, reduce the formation of interface holes, and improve the oxide film / coating bonding strength; it can also enhance the selective oxidation of Al, so that the critical Al content required to form a single Al2O3 on the coating surface is reduced; it can also hinder the diffusion of refractory elements in the substrate to the coating, hinder the formation of loose or volatile oxides, and improve the oxidation resistance of the fixture. Under the condition of 1220℃, the atomic diffusion coefficients of Al, Ta, Mo, Re, etc. in the alloy become larger, the atomic diffusion activation energy becomes smaller, and the element diffusion intensifies. The Ni3Al-based single crystal alloy directly contacts the sample to be tested at high temperature, which will cause the sample to be tested to bond with the fixture alloy. The YSZ ceramic layer provided on the surface of the gasket of the present invention can separate the Ni3Al-based single crystal alloy from the sample to be tested, forming a diffusion-blocking effect, and preventing the fixture alloy (Ni3Al-based single crystal alloy) from bonding with the sample to be tested. The fixture prepared with the Ni3Al-based single crystal alloy provided by the present invention can perform temperature resistance performance testing on the alloy at a temperature above 1200℃, and will not bond with the alloy to be tested, maintaining the smoothness of the surface of the alloy to be tested. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 A schematic diagram of the structure of the base in the fixture prepared in the embodiment;
[0032] Figure 2 A schematic diagram of the structure of a gasket in a fixture prepared in an embodiment;
[0033] Figure 3 The creep curve of the Ni3Al-based single crystal alloy prepared in Example 1 at 1220°C / 70MPa;
[0034] Figure 4 The microstructure of the Ni3Al-based single crystal alloy prepared in Example 1 after heat exposure at 1220°C for 1000h;
[0035] Figure 5 This is a physical picture of the base in the fixture prepared in Example 1;
[0036] Figure 6 This is a physical picture of the gasket in the fixture prepared in Example 1;
[0037] Figure 7 It is a schematic diagram of the assembly of using a fixture to clamp the sample to test the high temperature resistance of the alloy;
[0038] Figure 8 This is a longitudinal cross-sectional micrograph of the PtAl coating prepared on the fixture alloy;
[0039] Fig. 9 This is the oxidation weight gain curve of the fixture substrate + PtAl coating prepared in Example 1 in an atmospheric environment at 1220°C;
[0040] Fig.10 This is a comparison chart after creep experiment between gasket with diffusion barrier layer and gasket without diffusion barrier coating. DETAILED DESCRIPTION
[0041] The present invention provides a Ni3Al-based single crystal alloy, comprising the following element components in percentage by mass:
[0042]
[0043] In terms of mass percentage, the Ni3Al-based single crystal alloy provided by the present invention includes 7.0-8.3wt.% Al, which may be 8.0-8.3wt.%, and may specifically be 7.0wt.%, 7.3wt.%, 7.5wt.%, 7.8wt.%, 8.0wt.% or 8.3wt.%. In the present invention, the Al element is a forming element of the γ'-Ni3Al phase, and is a key element for increasing the "enrichment" of the γ'-Ni3Al phase. The increase in the Al content helps to increase the volume fraction of the γ'-Ni3Al phase, and can also improve the high-temperature oxidation resistance of the Ni3Al-based single crystal alloy.
[0044] In terms of mass percentage, the Ni3Al-based single crystal alloy provided by the present invention includes 2.0-3.8wt.% Ta, which may be 3.0-3.7wt.%, and may be specifically 2.0wt.%, 2.4wt.%, 2.6wt.%, 2.8wt.%, 3.0wt.%, 3.2wt.%, 3.5wt.% or 3.7wt.%. In the present invention, the Ta element is also a forming element of the γ'-Ni3Al phase, and is a key element for the "strengthening" of the γ'-Ni3Al phase. The increase in the Ta content helps to improve the ultra-high temperature thermal stability of the γ'-Ni3Al phase.
[0045] In terms of mass percentage, the Ni3Al-based single crystal alloy provided by the present invention includes 7.9-9.8wt.% Mo, which can be 8.5-9.0wt.%, and can be specifically 7.9wt.%, 8.0wt.%, 8.5wt.%, 8.8wt.%, 9.0wt.%, 9.3wt.%, 9.5wt.% or 9.8wt.%. In the present invention, the Mo element is a strengthening element of the γ-Ni phase, and is mainly distributed in the γ-Ni phase. The alloying design principle of "replacing part of Re with Mo" adopted in the present invention is the key to the low cost of the Ni3Al-based single crystal alloy. At the same time, the atomic radius of the Mo element is large, and lattice distortion is generated in the γ-Ni phase, which increases the mismatch of the Ni3Al-based single crystal alloy, generates a dense interface dislocation network, significantly hinders dislocation movement, and improves the high temperature durability of the Ni3Al-based single crystal alloy.
[0046] In terms of mass percentage, the Ni3Al-based single crystal alloy provided by the present invention includes 0.8-1.5wt.% Re, which may be 1.0-1.3wt.%, and may be specifically 0.8wt.%, 1.0wt.%, 1.3wt.% or 1.5wt.%. In the present invention, the Re element is a strengthening element of the γ-Ni phase, and is mainly distributed in the γ-Ni phase. When the Re element is enriched at the γ'-Ni3Al phase / γ-Ni phase interface, a "Re element cluster effect" is generated, which can significantly hinder the movement of dislocations and improve high-temperature endurance performance.
[0047] The Ni3Al-based single crystal alloy provided by the present invention includes the balance Ni in terms of mass percentage. In the present invention, the Ni element is a forming element of the γ-Ni phase and the γ'-Ni3Al phase.
[0048] In the present invention, the Ni3Al-based single crystal alloy includes a γ'-Ni3Al phase and a γ-Ni phase, and the volume fraction of the γ'-Ni3Al phase can be 76 to 80 vol.%, or 20 to 24 vol.%; the volume fractions of the γ'-Ni3Al phase and the γ-Ni phase in the Ni3Al-based single crystal alloy can be specifically as follows: the volume fraction of the γ'-Ni3Al phase is 78 vol.%, and the volume fraction of the γ-Ni phase is 22 vol.%.
[0049] The present invention also provides a method for preparing the Ni3Al-based single crystal alloy described in the above technical solution, comprising the following steps:
[0050] Mixing the materials according to the element ratio and smelting them to prepare a master alloy;
[0051] Remelting the master alloy and then performing single crystal casting to obtain an alloy blank;
[0052] The alloy blank is subjected to solution treatment and aging treatment in sequence to obtain the Ni3Al-based single crystal alloy.
[0053] In the present invention, unless otherwise specified, all materials are conventional commercially available products.
[0054] The present invention mixes materials according to the element ratio and smelts them to prepare a master alloy. The present invention has no special requirements for the aluminum source, tantalum source, molybdenum source, rhenium source and nickel source used to prepare the Ni3Al-based single crystal alloy, and conventional materials in the art can be used. As a specific embodiment of the present invention, the smelting can be vacuum induction melting. The present invention has no special limitation on the vacuum induction melting, and the smelting can be carried out in a conventional manner in the art.
[0055] After obtaining the master alloy, the present invention remelts the master alloy and then performs single crystal casting to obtain an alloy blank. As a specific embodiment of the present invention, the shape of the alloy blank can be cylindrical, the diameter of the cross section of the cylinder can be 32 mm, and the height of the cylinder can be 180 mm; the remelting and single crystal casting can be performed in the middle of a single crystal furnace. As a specific embodiment of the present invention, the crystal pulling rate of the single crystal casting can be 1 to 5 mm / s, or 2 to 4 mm / s, and can be specifically 1 mm / s, 1.5 mm / s, 2 mm / s, 2.5 mm / s, 3 mm / s, 3.5 mm / s, 4 mm / s, 4.5 mm / s or 5 mm / s. The present invention limits the crystal pulling rate within the above range to form the best dendrite structure and improve the mechanical properties of the Ni3Al-based single crystal alloy.
[0056] After obtaining the alloy blank, the present invention sequentially performs solution treatment and aging treatment on the alloy blank to obtain the Ni3Al-based single crystal alloy. As a specific embodiment of the present invention, the temperature of the solution treatment can be 1290-1335°C, and can be specifically 1290°C, 1300°C, 1310°C, 1320°C, 1330°C or 1335°C; the holding time of the solution treatment can be 20-30h, and can be specifically 20h, 22h, 25h, 28h or 30h. The present invention can eliminate dendrite segregation and achieve element homogenization through solution treatment; at the same time, it can dissolve the coarse primary γ' phase, γ / γ' eutectic phase and segregation phase in the dendrite during the casting process, creating conditions for the subsequent γ' phase precipitation transformation.
[0057] As a specific embodiment of the present invention, the solution treatment may further include: cooling the product after the solution treatment to room temperature; the cooling method may be air cooling, and the room temperature may be 20-30°C.
[0058] As a specific embodiment of the present invention, the aging treatment includes a primary aging treatment and a secondary aging treatment performed in sequence; the temperature of the primary aging treatment can be 1000-1100°C, and can be specifically 1000°C, 1010°C, 1020°C, 1030°C, 1040°C, 1050°C, 1060°C, 1070°C, 1080°C, 1090°C or 1100°C; the insulation time of the primary aging treatment can be 2-4h, and can be specifically 2h, 2.5h, 3h, 3.5h or 4h. As a specific embodiment of the present invention, the primary aging treatment can also include: cooling the product after the primary aging treatment to room temperature; the cooling method can be air cooling, and the temperature of the room temperature can be 20-30°C.
[0059] As a specific embodiment of the present invention, the temperature of the secondary aging treatment can be 850-900°C, and can be specifically 850°C, 860°C, 870°C, 880°C, 890°C or 900°C; the holding time of the secondary aging treatment can be 30-34h, and can be specifically 30h, 31h, 32h, 33h or 34h. As a specific embodiment of the present invention, the secondary aging treatment can also include: cooling the product after the secondary aging treatment to room temperature; the cooling method can be air cooling, and the temperature of the room temperature can be 20-30°C.
[0060] The present invention can adjust the morphology and size of the γ' phase through primary aging treatment; and can adjust the morphology of the γ' phase through secondary aging treatment, thereby improving the mechanical properties of the Ni3Al-based single crystal alloy. When the morphology of the γ' phase is cubic, it provides a stronger barrier to the movement of dislocations, and the creep performance of the alloy is relatively excellent. Under high temperature conditions, the size of the γ' phase is generally between 200nm and 500nm. When the γ' phase is too large, the γ' phase coarsening and merging rate is faster. When the γ' phase is too small, it dissolves faster at high temperature, which is not conducive to hindering the movement of dislocations.
[0061] The present invention adopts the organizational design idea of the synergistic effect of the two-phase organization of γ'-Ni3Al phase + γ-Ni phase, and adopts the alloying design idea of high Al-rich γ'-Ni3Al phase volume fraction and high Ta-strong γ'-Ni3Al phase to improve the ultra-high temperature thermal stability of γ'-Ni3Al. At the same time, combined with the high mismatch alloying synergistic control design using Mo instead of Re, the mismatch of γ'-Ni3Al and γ-Ni phases is fully controlled, the density of the interface dislocation network is increased, and the ultra-high temperature organizational stability is enhanced. At the same time, the temperature bearing capacity of Ni3Al single crystal intermetallic compounds is significantly improved, and the cost of the fixture alloy is reduced.
[0062] The present invention also provides the use of the Ni3Al-based single crystal alloy described in the above technical solution or the Ni3Al-based single crystal alloy prepared by the preparation method described in the above technical solution in a fixture used for preparing and testing the temperature resistance of the alloy.
[0063] The present invention also provides a clamp, comprising a base and a gasket;
[0064] The substrate comprises a first Ni3Al-based single crystal alloy and a PtAl coating coated on the surface of the first Ni3Al-based single crystal alloy;
[0065] The gasket comprises a second Ni3Al-based single crystal alloy and a HY3 coating and a YSZ ceramic layer which are sequentially laminated and coated on the surface of the second Ni3Al-based single crystal alloy;
[0066] The first Ni3Al-based single crystal alloy and the second Ni3Al-based single crystal alloy are the Ni3Al-based single crystal alloy described in the above technical solution or the Ni3Al-based single crystal alloy prepared by the preparation method described in the above technical solution.
[0067] The present invention has no special restrictions on the shape and size of the substrate and the gasket, and they can be designed according to the shape and size of conventional fixtures in the art; Figure 1 is a schematic diagram of the structure of the base in the fixture prepared in the embodiment, Figure 2 Schematic diagram of the structure of the gasket in the fixture prepared in the embodiment.
[0068] As a specific embodiment of the present invention, the thickness of the PtAl coating can be 35-40 μm; the thickness of the HY3 coating can be 30-50 μm, and can also be 35-45 μm. In the present invention, the HY3 coating has two main functions. First, its thermal expansion coefficient is between that of the gasket alloy (Ni3Al-based single crystal alloy) and the YSZ ceramic layer, which can effectively bond the gasket (Ni3Al-based single crystal alloy) and the YSZ ceramic layer; second, the HY3 coating has good anti-oxidation properties, which can prevent the gasket from oxidation.
[0069] As a specific embodiment of the present invention, the thickness of the YSZ ceramic layer can be 100-150 μm, or 110-140 μm. In the present invention, the YSZ ceramic layer mainly plays a diffusion barrier role, preventing the sample and the fixture from diffusing and bonding together during the ultra-high temperature test, thereby reducing the service life of the fixture.
[0070] The present invention also provides a method for preparing the clamp described in the above technical solution, comprising the following steps:
[0071] Processing the Ni3Al-based single crystal alloy to obtain a matrix model and a gasket model respectively;
[0072] Plating Pt, removing hydrogen, diffusing Pt and infiltrating Al are sequentially performed on the surface of the substrate model to obtain the substrate;
[0073] Spraying HY3 coating and YSZ ceramic layer on the surface of the gasket model in sequence to obtain the gasket;
[0074] The base and the gasket are assembled to obtain the clamp.
[0075] The present invention processes the Ni3Al-based single crystal alloy to obtain a matrix model and a gasket model respectively. The present invention has no special limitation on the processing, and conventional methods in the art can be used.
[0076] After obtaining the matrix model, the present invention sequentially performs Pt electroplating, hydrogen removal, Pt diffusion and Al infiltration treatment on the surface of the matrix model to obtain the matrix. As a specific embodiment of the present invention, the matrix model can also be pre-treated before electroplating Pt, and the pre-treatment can include the following steps: cleaning the matrix model and then performing surface activation treatment. As a specific embodiment of the present invention, the cleaning can be ultrasonic cleaning; the cleaning liquid for ultrasonic cleaning can be anhydrous ethanol; the temperature of the cleaning liquid can be 50-70°C, specifically 50°C, 55°C, 60°C, 65°C or 70°C; the time of the ultrasonic cleaning can be 20-40min, specifically 20min, 25min, 30min, 35min or 40min.
[0077] As a specific embodiment of the present invention, the surface activation treatment can be sandblasting the surface of the substrate model; the pressure of the sandblasting can be 0.2-0.4MPa, specifically 0.2MPa, 0.25MPa, 0.3MPa, 0.35MPa or 0.4MPa; the number of sandblasting meshes can be 120. The present invention can remove oil stains on the surface of the Ni3Al-based single crystal alloy through sandblasting on the one hand, thereby playing a cleaning role; on the other hand, it can improve the roughness of the surface of the Ni3Al-based single crystal alloy and increase the bonding force between the substrate model and the PtAl coating.
[0078] As a specific embodiment of the present invention, the Pt electroplating can be carried out in a Pt-containing bath using a constant current power supply; the current density of the electroplating can be 0.5 to 2 A / dm 2 , which can be specifically 0.5A / dm 2 , 1A / dm 2 , 1.5A / dm 2 or 2A / dm 2; The Pt-containing bath solution may be a P salt ([(NH3)2Pt(NO2)2·2H2O]) solution; The thickness of the Pt-plated layer formed by the electroplating may be 3 to 5 μm, specifically 3 μm, 4 μm or 5 μm. The present invention has no special limitation on the electroplating time, as long as a Pt layer of the required thickness can be formed. In the present invention, electroplating Pt is a key step in the preparation of PtAl coatings. The role of Pt has three main aspects: first, inhibiting the "sulfur effect", that is, inhibiting the aggregation of S at the interface between the oxide film and the coating, reducing the formation of interface pores, and improving the oxide film / coating bonding; second, enhancing the selective oxidation of Al, thereby reducing the critical Al content required to form a single Al2O3 on the coating surface; third, hindering the diffusion of refractory elements in the matrix into the coating, thereby hindering the formation of loose or volatile oxides.
[0079] As a specific embodiment of the present invention, the dehydrogenation can be carried out using a vacuum heat treatment furnace, the dehydrogenation temperature can be 390-460°C, or 400-450°C; the dehydrogenation insulation time can be 5-6h; the dehydrogenation vacuum degree can be 1×10 -5 Pa or less, specifically 1×10 -5 Pa.
[0080] As a specific embodiment of the present invention, the Pt diffusion can be performed by vacuum heat treatment. The temperature of the Pt diffusion can be 990-1060°C, or 1000-1050°C. The insulation time of the Pt diffusion can be 2-4h, or specifically 2h, 3h or 4h. The vacuum degree of the Pt diffusion can be lower than 1×10 -4 Pa, can also be 1×10 -5 Pa.
[0081] As a specific embodiment of the present invention, the Al-infiltrating treatment can be carried out using a vapor phase Al-infiltrating furnace, the Al-infiltrating treatment temperature can be 930-970°C, or 940-960°C; the Al-infiltrating treatment time can be 4-6 hours, or specifically 4 hours, 5 hours, or 6 hours. The present invention forms a PtAl coating by aluminum-infiltrating the surface of the electroplated Pt layer. The excellent oxidation resistance of the PtAl coating mainly comes from the oxidation of the Al element to form a dense α-Al2O3 film, which prevents O atoms from further diffusing and oxidizing the matrix.
[0082] After obtaining the gasket model, the present invention sequentially sprays HY3 coating and YSZ ceramic layer on the surface of the gasket model to obtain the gasket. As a specific embodiment of the present invention, the gasket model can also be pre-treated before spraying the HY3 coating, and the pre-treatment can include the following steps: performing surface activation treatment on the gasket model. As a specific embodiment of the present invention, the surface activation treatment can be sandblasting the surface of the gasket model; the pressure of the sandblasting can be 0.2-0.4MPa, which can be specifically 0.2MPa, 0.25MPa, 0.3MPa, 0.35MPa or 0.4MPa; the sandblasting mesh number can be 60-80#, and can also be 65-75#. The present invention can remove oil stains on the surface of Ni3Al-based single crystal alloy through sandblasting on the one hand, thereby playing a cleaning role; on the other hand, it can improve the roughness of the surface of Ni3Al-based single crystal alloy and increase the bonding force between the gasket model and the HY3 coating.
[0083] As a specific implementation of the present invention, the method of spraying the HY3 coating may be atmospheric plasma spraying. The present invention has no special limitation on the atmospheric plasma spraying, and the spraying may be performed in a conventional manner in the art.
[0084] As a specific embodiment of the present invention, the method of spraying the YSZ ceramic layer can be atmospheric plasma spraying. The present invention has no special limitation on the atmospheric plasma spraying, and the spraying can be carried out in a conventional manner in the art.
[0085] After obtaining the base and the gasket, the present invention assembles the base and the gasket to obtain the clamp. The present invention has no special limitation on the assembly, and a conventional method in the art can be used.
[0086] The present invention also provides the application of the fixture described in the above technical solution in detecting the temperature resistance of alloys. The fixture prepared by using the Ni3Al-based single crystal alloy provided by the present invention can be used at temperatures of 1220°C and above, effectively filling the gap of existing creep fixtures at 1220°C and above. At the same time, the present invention significantly improves the oxidation resistance of the fixture alloy in combination with the anti-oxidation coating design. On the other hand, the ceramic-coated high-temperature resistant gasket effectively solves the mutual diffusion problem between the sample to be tested and the fixture.
[0087] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0088] Example 1
[0089] Aluminum source, tantalum source, molybdenum source, rhenium source and nickel source are mixed according to element ratio and then subjected to vacuum induction melting to obtain a master alloy; the master alloy is remelted in a single crystal furnace and then single crystal casting is performed (crystal pulling rate is 3 mm / s) to obtain a Φ32×180 mm alloy blank (single crystal rod);
[0090] The alloy blank is kept at 1330°C for 25 hours for solution treatment and then air-cooled to 25°C; the product after solution treatment is kept at 1020°C for 2 hours for primary aging treatment and then air-cooled to 25°C; the product after primary aging treatment is kept at 870°C for 32 hours for secondary aging treatment and then air-cooled to 25°C to obtain a Ni3Al-based single crystal alloy, the element content of the Ni3Al-based single crystal alloy is 8.3wt.%Al, 3.7wt.%Ta, 8.5wt.%Mo, 1wt.%Re and balance Ni.
[0091] Prepare the fixture as follows:
[0092] according to Figure 1 and Figure 2 The prepared Ni3Al-based single crystal alloy is processed to obtain a matrix model and a gasket model respectively;
[0093] The substrate model was placed in anhydrous ethanol cleaning solution at a temperature of 50°C for 30 minutes and then ultrasonically cleaned. The surface was sandblasted at a pressure of 0.3 MPa and a mesh size of 120. A constant current power supply was used with a current density of 1 A / dm 2 The surface of the substrate model after sandblasting is electroplated with Pt in a Pt-containing bath solution (P salt solution) to obtain a Pt-plated layer with a thickness of 3 μm; the substrate model after Pt plating is placed in a vacuum heat treatment furnace at a temperature of 400°C and a pressure of 1×10 -5 The product after dehydrogenation was heated at 1040℃ and 1×10 -5 The Pt diffusion is performed for 2 hours under a vacuum degree of Pa; the product after the Pt diffusion is placed in a vapor phase Al diffusion furnace and Al-diffused for 6 hours at 960° C. to form a PtAl coating to obtain a substrate;
[0094] The surface of the gasket model is sandblasted, the sandblasting pressure is 0.3 MPa, and the sandblasting mesh is 120 mesh; the surface of the gasket model after sandblasting is subjected to atmospheric plasma spraying to form a HY3 coating with a thickness of 45 μm; the surface of the HY3 coating is subjected to atmospheric plasma spraying to form a YSZ ceramic layer with a thickness of 120 μm, thereby obtaining the gasket;
[0095] The base and the gasket are assembled to obtain a fixture.
[0096] Example 2
[0097] A Ni3Al-based single crystal alloy is prepared according to the method of Example 1, except that the element content of the Ni3Al-based single crystal alloy is 8.3wt.% Al, 3.7wt.% Ta, 8.0wt.% Mo, 1wt.% Re and the balance Ni.
[0098] The fixture was prepared according to the method of Example 1, except that the raw material for preparing the substrate and the gasket was the Ni3Al-based single crystal alloy prepared in Example 2.
[0099] Comparative Example 1
[0100] Prepare a Ni3Al-based single crystal alloy according to the method of Example 1;
[0101] according to Figure 1 and Figure 2 The prepared Ni3Al-based single crystal alloy is processed to obtain a substrate and a gasket respectively; the substrate and the gasket without coating on the surface are directly used as a fixture.
[0102] The Ni3Al-based single crystal alloy prepared in Example 1 was subjected to creep property testing at a temperature of 1220°C and a pressure of 70 MPa to obtain a creep curve, as shown in FIG. Figure 3 As shown. Figure 3 It can be seen that the Ni3Al-based single crystal alloy has a long life of up to 124h under the conditions of 1220℃ and 70MPa, and has excellent high-temperature resistant mechanical properties.
[0103] The Ni3Al-based single crystal alloy prepared in Example 1 was subjected to a microstructure stability test after being heat-exposed at 1220°C for 1000 hours, and a microstructure diagram of the fixture alloy after being heat-exposed at 1220°C for 1000 hours was obtained. Figure 4 As shown. Figure 4 It can be seen that the two phases are accompanied by a certain degree of merging and coarsening growth, in which the average size of the γ phase is about 0.56μm, and the average size of the γ' phase is about 2.68μm. The coarsening growth rate of the two phases is slow, and the fixture alloy has excellent microstructure stability.
[0104] The Ni3Al-based single crystal alloy prepared in Examples 1 to 2 was placed in a high temperature creep tester, and its stress and endurance life were tested under different temperature and stress conditions in accordance with "HB5150-1996 Metal Material Tensile Creep and Endurance Test Methods". The results are listed in Table 1.
[0105] Table 1 Properties of Ni3Al-based single crystal alloys prepared in Examples 1 and 2
[0106]
[0107]
[0108] Combining Table 1 and Figure 3 , 4 It can be seen that the Ni3Al-based single crystal alloy provided by the present invention has excellent high temperature resistance.
[0109] Figure 5 This is a physical picture of the base component in the fixture prepared in Example 1. Figure 6 The figure is a physical picture of the gasket component in the fixture prepared in Example 1. The assembly diagram of using the fixture to clamp the sample to test the high temperature resistance of the alloy is as follows Figure 7 shown.
[0110] The fixture substrate prepared in Example 1 was subjected to a PtAl coating preparation state microstructure test to obtain a longitudinal cross-sectional microstructure diagram of the PtAl coating, as shown in FIG. Figure 8 As shown. Figure 8 It can be seen that the PtAl coating on the substrate surface includes a four-layer structure, namely, a Mo-rich interdiffusion zone, a Pt-rich diffusion zone, a NiPtAl+PtAl2 dual-phase zone, and a NiPtAl single-phase zone.
[0111] The PtAl coated substrate prepared in Example 1 was placed in an atmosphere at 1220°C for oxidation resistance testing, and the weight was measured every 20 hours. The oxidation weight gain curve is shown in FIG. Fig. 9 As shown. According to the weight gain curve, the antioxidant rate is calculated to be 0.0612g / (m 2 h), reaching the complete antioxidant level.
[0112] The diffusion resistance effect of the gaskets prepared in Example 1 and Comparative Example 1 was tested to obtain a diffusion resistance comparison diagram of the gasket with a diffusion resistance layer and the gasket without a diffusion resistance coating, as shown in FIG. Fig.10 As shown, the left side is the test result of Example 1, and the right side is the test result of Comparative Example 1. Fig.10 It can be seen that the gasket in the left picture is not oxidized, and no diffusion occurs between the gasket and the sample. In the right picture, the gasket is severely oxidized, and the gasket and the sample are diffused and bonded together, indicating that the gasket provided by the present invention has a significant diffusion resistance effect.
[0113] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A Ni3Al-based single crystal alloy, characterized in that: Includes the following elemental components in mass percentage:
2. The Ni3Al-based single crystal alloy according to claim 1, characterized in that: Includes the following elemental components in mass percentage:
3. The method for preparing the Ni3Al-based single crystal alloy according to claim 1 or 2, characterized in that: The following steps are involved: Mixing the materials according to the element ratio and smelting them to prepare a master alloy; Remelting the master alloy and then performing single crystal casting to obtain an alloy blank; The alloy blank is subjected to solution treatment and aging treatment in sequence to obtain the Ni3Al-based single crystal alloy.
4. The preparation method according to claim 3, characterized in that: The temperature of the solution treatment is 1290-1335° C., and the holding time is 20-30 hours.
5. The preparation method according to claim 3, characterized in that: The aging treatment includes a primary aging treatment and a secondary aging treatment performed sequentially; The temperature of the primary aging treatment is 1000-1100°C, and the holding time is 2-4h; The temperature of the secondary aging treatment is 850-900° C., and the insulation time is 30-34 hours.
6. The preparation method according to claim 3, characterized in that: The crystal pulling rate of the single crystal casting is 1 to 5 mm / s.
7. Use of the Ni3Al-based single crystal alloy according to claim 1 or 2 or the Ni3Al-based single crystal alloy prepared by the preparation method according to any one of claims 3 to 6 in a fixture used for preparing and testing the heat resistance of the alloy.
8. A clamp, characterized in that: Including a substrate and a gasket; The substrate comprises a first Ni3Al-based single crystal alloy and a PtAl coating coated on the surface of the first Ni3Al-based single crystal alloy; The gasket comprises a second Ni3Al-based single crystal alloy and a HY3 coating and a YSZ ceramic layer which are sequentially laminated and coated on the surface of the second Ni3Al-based single crystal alloy; The first Ni3Al-based single crystal alloy and the second Ni3Al-based single crystal alloy are the Ni3Al-based single crystal alloy according to claim 1 or 2 or the Ni3Al-based single crystal alloy prepared by the preparation method according to any one of claims 3 to 6.
9. The method for preparing the clamp according to claim 8, comprising the following steps: Processing the Ni3Al-based single crystal alloy to obtain a matrix model and a gasket model respectively; Plating Pt, removing hydrogen, diffusing Pt and infiltrating Al are sequentially performed on the surface of the substrate model to obtain the substrate; Spraying HY3 coating and YSZ ceramic layer on the surface of the gasket model in sequence to obtain the gasket; The base and the gasket are assembled to obtain the clamp.
10. Use of the fixture according to claim 8 or the fixture prepared by the preparation method according to claim 9 in detecting the temperature resistance of alloys.
Citation Information
Patent Citations
Protective coating of single crystal high-temperature alloy as well as preparation method thereof
CN103552311A
Thermal barrier coating with stable interface and manufacturing method of thermal barrier coating
CN105463453A
Single crystal alloy for ultrahigh-temperature creep fixture, and preparation method thereof
CN113529172A
Thermal barrier coating with composite structure as well as preparation method and application of thermal barrier coating
CN116516290A
Ni3Al-based single crystal alloy and preparation method and application thereof
CN117626058A